Evolution of teachers' salaries in Latin America at the turn of the 20th century: How much are they (under or over) paid? - Alejandra Mizala; Hugo \~Nopo (Institute for the Study of Labor (IZA), 2012)
How much are teachers paid in comparison to those in other professions in Latin America? How have these differences evolved at the turn of the 20th century? This paper reports the evolution, between circa 1997 and circa 2007, of teachers' salaries vis-à-vis workers in other professional and technical occupations for thirteen Latin-American countries. After controlling the earnings differentials by observable characteristics linked to productivity it is found that the hourly earnings gap, although substantial, decreased throughout the decade. This has been the case for earnings gaps at the main and secondary jobs, and also for those measured in terms of monthly and yearly earnings. Nonetheless, behind the region averages there is an important cross-country heterogeneity.
Keywords: J31; J44; J8; O54; 330; wage differentials; professional labor markets; national and international labor standards; Latin America; Caribbean